Neuroprotective Actions of Cannabinoids in the Bovine Isolated Retina: Role of Hydrogen Sulfide - Leah Bush; Anthonia Okolie; Jenaye Robinson; Fatima Muili; Catherine A. Opere; Sunny E. Ohia; Ya Fatou Njie Mbye (Pharmaceuticals)
Both hydrogen sulfide and endocannabinoids can protect the neural retina from toxic insults under in vitro and in vivo conditions. Purpose: The aim of the present study was two-fold: (a) to examine the neuroprotective action of cannabinoids [methanandamide and 2-arachidonyl glycerol (2-AG)] against hydrogen peroxide (H2O2)-induced oxidative damage in the isolated bovine retina and (b) to evaluate the role of endogenously biosynthesized hydrogen sulfide (H2S) in the inhibitory actions of cannabinoids on the oxidative stress in the bovine retina. Methods: Isolated neural retinas from cows were exposed to oxidative damage using H2O2 (100 µM) for 10 min. When used, tissues were pretreated with methanandamide (1 nM–100 nM) and 2-AG (1–10 µM) for 30 min before a 10 min treatment with H2O2 (100 µM). In some experiments, retinas were pretreated with inhibitors of the biosynthesis of H2S [cystathionine β-synthase/cystathionine γ-lyase (CBS/CSE), aminooxyacetic acid, AOAA 30 µM, or 3-mercaptopyruvate sulfurtransferase (3MST), α-keto-butyric acid, KBA 1 mM] and the CB1-receptor antagonist, AM251 (100 nM) for 30 min before treatment with methanandamide (1 nM–100 µM). Enzyme immunoassay measurement of 8-epi PGF2α (8-isoprostane) levels was performed to assess lipid peroxidation in retinal tissues. Results: In the presence of H2O2 (100 µM), methanandamide (1 nM–100 µM) and 2-AG (1–10 µM) significantly (p < 0.001) blocked the H2O2-induced elevation in 8-isoprostane levels in the isolated bovine retina. In the presence of the CB1 antagonist AM251 (100 nM), the effect of methanandamide (1 nM) on the H2O2-induced 8-isoprostane production was significantly (p < 0.001) attenuated. While AOAA (30 µM) had no significant (p > 0.05) effect on the inhibition of H2O2-induced oxidative stress elicited by methanandamide, KBA (1 mM) reversed the neuroprotective action of methanandamide. Conclusions: The cannabinoids, methanandamide and 2-AG can prevent H2O2-induced oxidative stress in the isolated bovine retina. The neuroprotective actions of cannabinoids are partially dependent upon the activation of the CB1 receptors and endogenous production of H2S via the 3-MST/CAT pathway.